MODELS OF BUILDING COMMUNICATIONS IN ELECTRONIC SYSTEMS OF INCLUSIVE EDUCATION - PALAMARCHUK, YEVHEN; CHERESHNYUK, OLEKSII; KOVALENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the problems of building electronic learning systems (ELS) for inclusive forms of education, taking into account the special needs of individuals and their learning trajectories. Electronic learning systems (e-Learning) should provide not only access to educational materials, but also support active interaction between students, teachers and administrators. The interaction of individuals with ELS, algorithms of human-machine interaction for the main cases of inclusion are considered. Methods and approaches to creating effective interfaces that provide equal access to knowledge, support, interaction with teachers and other participants in the educational process are investigated. The purpose of the study is to determine the tools and form an adaptive interface for groups of applicants with inclusion who study in a distance or blended mode. Approaches to choosing tools for different types of inclusion are also analyzed. The general architecture of the hardware and software complex and the method of configuring the interface for different types of inclusion are proposed. formation of the architecture of interactive communication educational platforms in the perspective of promoting individualization of learning and creating conditions for socialization of students with inclusion.The results of the work can be used for developers of educational platforms, teachers and researchers, as well as for university management in the implementation of electronic educational systems and complexes adapted to inclusion. As a result of the research, a model and communication scenarios for implementing inclusive education in electronic learning systems were developed, along with an auxiliary hardware and software complex. An example of utilizing this software complex for individuals with special needs in a general inclusive environment for learning foreign languages was provided. The requirements for the interface were analyzed, and a basic layout was created.Future research plans include the development of a table that aligns interface elements with the communication features relevant to interactions with services and teachers during inclusive learning.
Keywords: learning management system; inclusive education; electronic learning system; communications model; learning platform architecture